2018
DOI: 10.1002/cche.10055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high‐intensity ultrasound pretreatment with different levels of power output on the antioxidant properties of alcalase hydrolyzates from Quinoa (Chenopodium quinoa Willd.) protein isolate

Abstract: Background and objectives:The effects of ultrasound pretreatment with different levels of power output (200, 400, and 600 W) on hydrolysis degree of Quinoa protein isolate (QPI) and antioxidant activity of QPI hydrolyzate were studied.The secondary structure, surface hydrophobicity, intrinsic fluorescence, and scanning electron microscopy (SEM) of QPI treated by ultrasound were measured.The untreated QPI and high-temperature treatment (90°C for 30 min) were used as control. Findings:The results showed that ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 36 publications
4
16
2
Order By: Relevance
“…The antioxidant activity was evaluated using the DPPH and ABTS methods. QPI-H400 (6 mg/mL) present high antioxidant activity with a value of DPPH of 80% RSA and QPI-H400 (2 mg/mL) present high antioxidant activity using the ABTS method with a value of 80% RSA [47].…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant activity was evaluated using the DPPH and ABTS methods. QPI-H400 (6 mg/mL) present high antioxidant activity with a value of DPPH of 80% RSA and QPI-H400 (2 mg/mL) present high antioxidant activity using the ABTS method with a value of 80% RSA [47].…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant activity of fish peptides prepared by microwave pretreatment (5 min) followed by conventional enzymatic hydrolysis (2-10 min) is superior to other treatment methods. The ultrasound can form the microbubbles in the liquid medium, and its rupture is accompanied by the release of energy, which can affect protein rearrangements and aggregate formation, thereby improving the biological activity of the hydrolysate [100][101][102][103]. The effect of ultrasonic and heat treatment on the enzymatic hydrolysis of barley beer waste protein by Alcalase showed that the ultrasonic pretreatment (50 kHz) can increase the antioxidant activity of protein hydrolysates and promote the release of PAs [104].…”
Section: Sourcementioning
confidence: 99%
“…As shown in Fig. 2a-e, the antioxidant properties of hydrolysates from HPI are much lower than the glutathione at the concentration of 1 mg/mL, but higher than hydrolysates from pea protein isolates (Girgih et al 2015) and hydrolysates from Quinoa protein (Li et al 2018) at the similar concentration. This result indicated that HPI can be used as sources of antioxidant peptides.…”
Section: Antioxidant Properties Of Hydrolysatesmentioning
confidence: 88%
“…The ultrasound has been widely used to modify protein structure and functional properties. Several papers have reported on the application of ultrasound treatment to increase the enzymatic hydrolysis of proteins (Chen et al 2011;Li et al 2018;Yang et al 2017). It has been suggested that ultrasonic treatment could induce alterations in tertiary or secondary structure and more hydrolysis sites were then exposed (Gülseren et al 2007;Güzey et al 2006;Xue et al 2017).…”
Section: Introductionmentioning
confidence: 99%